Genomic regions associated with adaptive and productive traits in Tibetan and Poll Dorset sheep - CGIAR Research Program on Livestock (2021)
The identification of genome-wide selection signatures can provide insights on the mechanisms of natural and/or artificial selection and uncover genes related to biological functions and/or phenotypes. The research provides a greater understanding of genome diversity and variations associated with adaptive and production traits in sheep.